Meta-analysis of Weight Change in the Placebo Arm of RCT’s for Weight Loss: Methods and Pilot Study - McNellis, Jennie L. (The University of Arizona., 2008)
Class of 2008 Abstract === Objectives: 1) To determine if data on weight change in the placebo arm of RCT's for weight loss were available, and 2) to conduct a pilot meta-analysis to estimate the average weight change in the placebo arm. Methods: Four randomized placebo controlled trials of rimonabant for weight loss were retrieved. A draft data extraction form was developed to record weight loss and demographic data. Potential for bias was assessed on design issues related to withdrawals, blinding, allocation procedure, adherence, and manufacturer influence. Based on available data, a forest plot was constructed and heterogeneity was assessed. The a priori alpha level was 0.05. Results: The placebo groups from all studies were similar. The pooled data indicated that individuals in the placebo arm lost an average of 3.3 kg, p < 0.001. One study had a significantly greater completion rate than the other studies. Participants were prescribed a hypocaloric diet and were instructed to increase physical activity but no data were reported on calories consumed or amount of physical activity. Weight loss of 5% ranged from 15-20% of participants. There was potential for bias relating to reported adherence, allocation concealment process, and manufacturer funding. Conclusions: Participants in the placebo arm of rimonabant trials lost an average of 3.3 kg, which was statistically significant. Little can be learned about weight loss in the placebo arm because no data on calories consumed, amount of exercise, or hunger were reported. Information from other RCT's is needed to provide additional data and to confirm the findings.